2020
DOI: 10.1051/0004-6361/202038054
|View full text |Cite
|
Sign up to set email alerts
|

Connecting measurements of solar and stellar brightness variations

Abstract: Context. A comparison of solar and stellar brightness variations is hampered by the difference in spectral passbands that are used in observations, and also by the possible difference in the inclination of the solar and stellar rotation axes from the line of sight. Aims. We calculate the rotational variability of the Sun as it would be measured in passbands used for stellar observations. In particular, we consider the filter systems used by the CoRoT, Kepler, TESS, and Gaia space missions. We also quantify the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Compared to the Keplerband results, TESS-band variability is lower for all spectral types and coverage levels. This is a direct consequence of the spot and facular contrasts being smaller in redder wavelength intervals (Nèmec et al 2020b).…”
Section: Tess-band Variabilitymentioning
confidence: 98%
“…Compared to the Keplerband results, TESS-band variability is lower for all spectral types and coverage levels. This is a direct consequence of the spot and facular contrasts being smaller in redder wavelength intervals (Nèmec et al 2020b).…”
Section: Tess-band Variabilitymentioning
confidence: 98%
“…Next, the facular coverages were obtained by first, subtracting the magnetic flux of the spots from the magnetograms and then using the remaining flux to calculate the faculae areas following the approach of Krivova et al (2003) of setting a saturation threshold B sat . While we used the SFTM simulations from Cameron et al (2010) in N20b and Nèmec et al (2020a), the results in this study are based on the model in I18 in the present work. We discuss the differences in these two models in more detail in the next section.…”
Section: Surface Flux Transport and Filling Factorsmentioning
confidence: 99%
“…For example, Nèmec et al (2020b) have combined the Spectral And Total Irradiance Reconstruction (SATIRE, Fligge et al 2000, Krivova et al 2003) model together with a surface flux transport model (SFTM, Cameron et al 2010) to model the power spectra of solar brightness variations at various inclinations down to several days. This approach allowed to remove a number of important observational biases when comparing the solar variability to that of other stars (Nèmec et al 2020a. By employing the Nèmec et al (2020b) model, Reinhold et al (2021 have found that rotation periods of most of the G-dwarfs of near-solar age go undetected.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the rotation induced changes in the fractional coverage by faculae decreases as the inclination decreases and the variation produced by rotation disappears at i = 0 °(see e.g. Figure 7 of Nèmec et al 2020a). At i = 0 °the faculae simply move along in circles staying at roughly the same limb distances instead of crossing all µ values as at i = 90 °.…”
Section: Variations On the Rotational Timescalementioning
confidence: 97%
“…The cycle averages follow the same trend as the cycle maximum, as does the amplitude of the S-index variations. The horizontal dashed lines show the values averaged over all inclinations computed using (as done by Nèmec et al 2020a)…”
Section: Variations On the Activity Cycle Timescalementioning
confidence: 99%